Оптимизация систем в условиях интервальной неопределенности - Левин, В. И. (Видавництво Львівської політехніки, 2011)
Optimization problems at the indeterminacy is touched. The review of some works in this field is given. Most simple and natural case - interval indeterminacy, when parameters of system are intervals - is considered.
Keywords: optimization; systems; indeterminacy; interval; comparison; continuous logic